Ochotona princeps - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Ochotona princeps (Richardson, 1828). Zool. J., 3:520. TYPE LOCALITY: Canada, Alberta, near Athabasca Pass, head of Athabasca River. DISTRIBUTION: Mountains of W. North America from C. British Columbia (Canada) to N. New Mexico, Utah, C. Nevada, and E.C. California (U.S.A.). COMMENT: Broadbooks, 1965, Am. Midi. Nat., 299-335, and Youngman, 1975, Mammals of the Yukon Terr., Nat. Mus. Nat. Sci. (Ottawa), Publ. Zool. 10, 192 pp., considered princeps and collaris conspecific. Corbet, 1978, following Gureev, 1964, included princeps in alpina. A statistical re-evaluation of craniometric data by Weston, 1981, in Myers, Proc. World Lagomorph Conf., indicated that princeps, collaris, and alpina are separate species. See also comments under alpina. ISIS NUMBER: 5301409001001008001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Lagomorpha, pp. 595-604 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on pages 596-597, DOI: 10.5281/zenodo.7353003